2002
DOI: 10.1152/ajpendo.00047.2002
|View full text |Cite
|
Sign up to set email alerts
|

KATP channels and insulin secretion disorders

Abstract: ATP-sensitive potassium (K(ATP)) channels are inhibited by intracellular ATP and activated by ADP. Nutrient oxidation in beta-cells leads to a rise in [ATP]-to-[ADP] ratios, which in turn leads to reduced K(ATP) channel activity, depolarization, voltage-dependent Ca(2+) channel activation, Ca(2+) entry, and exocytosis. Persistent hyperinsulinemic hypoglycemia of infancy (HI) is a genetic disorder characterized by dysregulated insulin secretion and, although rare, causes severe mental retardation and epilepsy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
126
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 73 publications
2
126
0
Order By: Relevance
“…Although only limited data are available, there are reports that some CHI patients, even those non-surgically treated, can spontaneously progress to diabetes [7,48,49]. In addition, we have shown that normally hypersecreting Kir6.2[AAA] transgenic mice on a Kir6.2 +/− background (which, although untested, presumably have a greater reduction in K ATP channel activity than each genotype alone), but not Kir6.2 +/− mice, can progress from a hypersecreting phenotype to an undersecreting diabetic phenotype, when challenged by a highfat diet [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although only limited data are available, there are reports that some CHI patients, even those non-surgically treated, can spontaneously progress to diabetes [7,48,49]. In addition, we have shown that normally hypersecreting Kir6.2[AAA] transgenic mice on a Kir6.2 +/− background (which, although untested, presumably have a greater reduction in K ATP channel activity than each genotype alone), but not Kir6.2 +/− mice, can progress from a hypersecreting phenotype to an undersecreting diabetic phenotype, when challenged by a highfat diet [18].…”
Section: Discussionmentioning
confidence: 99%
“…Naively, reduced or absent K ATP channel activity is expected to result in constitutive membrane depolarisation, elevated [Ca 2+ ] i and hypersecretion of insulin. In humans, heterozygous loss-of-function mutations of beta cell K ATP subunits (SUR1, encoded by the gene ABCC8, and Kir6.2, encoded by the gene KCNJ11) underlie congenital hyperinsulinaemia (CHI) [1][2][3][4][5][6][7], a rare genetic disease characterised by relative hyperinsulinaemia, which generally presents with high insulin levels in parallel with low blood glucose [8].…”
mentioning
confidence: 99%
“…Huopio et al 2002). Consequently, K ATP channels are always closed, independent of the metabolic state of the cell.…”
Section: When Regulation Fails: Sur1 Mutations and Diseasementioning
confidence: 99%
“…A rise in circulating insulin, in turn, leads to an increased peripheral glucose uptake and compensatory drop in blood glucose. Conversely, a falling intracellular [ATP]͞ [ADP] ratio during the fasting state is presumed to relieve inhibition of K ATP channels, resulting in membrane hyperpolarization and cessation of Ca 2ϩ -induced insulin release (3).…”
mentioning
confidence: 99%
“…Profound neonatal diabetes due to permanent suppression of insulin release is observed in transgenic mice expressing overactive beta cell K ATP channels, dramatically illustrating the ability of K ATP channels to inhibit secretion (8). Conversely, the recent discovery of numerous mutations in pancreatic K ATP channel subunits (both the poreforming Kir6.2 and SUR1) in human patients with persistent hyperinsulinemic hypoglycemia of infancy (PHHI) (3) establishes a causative link between suppressed K ATP activity, and the corollary metabolic disorder of hyperinsulinism (3). PHHIassociated K ATP mutations can be classified into two major categories: those that suppress channel activity without altering cell-surface expression, and biosynthetic or trafficking defects that reduce or abolish surface expression.…”
mentioning
confidence: 99%